2021
DOI: 10.1007/s00429-020-02201-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of the mouse anterior amygdalar radial unit marked by Lhx9-expression

Abstract: The amygdala in mammals plays a key role in emotional processing and learning, being subdivided in pallial and subpallial derivatives. Recently, the cortical ring model and the pallial amygdalar radial model (Puelles et al. 2019; Garcia-Calero et al. 2020) described the pallial amygdala as an histogenetic field external to the allocortical ring, and subdivided it in five major radial domains called lateral, basal, anterior, posterior and retroendopiriform units. The anterior radial unit, whose cells typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 91 publications
(296 reference statements)
2
31
0
Order By: Relevance
“…This new, much more complex amygdalar model now explains easily the previously contradictory data of Gorski et al (2002), Puelles (2014) and Puelles et al (2016c). Garcia-Calero andPuelles (2021) reexamined and reinterpreted the Dbx1 data of Puelles et al (2016c) within the novel radial amygdalar model. They reached the conclusion, consistent with both radial glia pattern and Bielle et al.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This new, much more complex amygdalar model now explains easily the previously contradictory data of Gorski et al (2002), Puelles (2014) and Puelles et al (2016c). Garcia-Calero andPuelles (2021) reexamined and reinterpreted the Dbx1 data of Puelles et al (2016c) within the novel radial amygdalar model. They reached the conclusion, consistent with both radial glia pattern and Bielle et al.…”
Section: Discussionmentioning
confidence: 92%
“…7i-l; ). We hybridized in situ some sections of the horizontal series with the Lhx9 probe, which selectively labels the BMA and ACo nuclei of the anterior amygdalar radial unit, as well as the neighboring ventral subdivision of medial amygdala and the anterior amygdala Garcia-Calero and Puelles 2021). We also examined the distribution of the subpallial marker Dlx5, whose signal is absent from the NLOT2 and its migration stream (Fig.…”
Section: Description Of the Tbr1-expressing Nlot2 Migratory Stream In The Context Of Sim1 Expression In The Telencephalic Vesiclementioning
confidence: 99%
See 1 more Smart Citation
“…Given that Emx1 is expressed in the anlagen of the BL and the PLCo ( Puelles et al, 2000 ; Medina et al, 2004 ), whereas Pax6 within the BM ( Puelles et al, 2000 ) and the Me ( Bupesh et al, 2011 ; Duan et al, 2013 ), we identified the dorsal Pax6 / Tbr2 expressing focus as the BM anlage. Moreover, we considered the superficial Tbr2 -expressing domain to represent superficial corticoid nuclei (ACo), given (1) its position between the Emx1 positive BL/PLCo and the Emx1 / Tbr1 negative Me primordia and (2) the fact that both BMA and ACo are products of the anterior amygdalar radial unit ( Garcia-Calero and Puelles, 2021 ). On the other hand, it could belong to the MePV, given that its core has been reported to express both Pax6 and Tbr2 ( Ruiz-Reig et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Functional expression of this gene in the adult hypothalamus has been recently linked to regulation of metabolism 21 . Lhx9 and Isl1 are transcription factors which also have roles in neurodevelopment 22, 23 . Fibcd1 belongs to a class of proteins known as fibrinogen-related domains (FreD) with multiple functions which include innate immunity and are expressed in glial cells in the human brain 24 .…”
Section: Main Textmentioning
confidence: 99%